Suicidality and Quality of Life in Treatment-Resistant Depression Patients in Latin America: Secondary Interim Analysis of the TRAL Study - Corral, Ricardo; Alessandria, Hernan; Agudelo Baena, Lina María; Ferro, Eugenio; Duque, Xochitl; Quarantini, Lucas; Caldieraro, Marco Antonio; Cabrera, Patricia; Kanevsky, Gabriela (Frontiers in Psychiatry, 2022)
Background: A large proportion of patients with major depressive disorder (MDD) have treatment-resistant depression (TRD). The TRAL study examines the impact of TRD on suicidality and health-related quality of life (HRQoL) among MDD patients in 4 Latin American countries. Methods: In this multicenter, prospective, observational study, MDD patients were recruited from 33 sites in Mexico, Colombia, Brazil, and Argentina. Patients were assessed for TRD, defined as failure to respond to ≥2 antidepressant medications of adequate dose and duration. Other assessments included current disease status, Mini International Neuropsychiatric Interview (MINI), Columbia-Suicide Severity Rating Scale (C-SSRS), 5 Level EQ-5D (EQ-5D-5L), Patient Health Questionnaire-9 (PHQ-9), and Sheehan Disability Scale (SDS). Results: 1,475 MDD patients were included in the analysis (mean age, 45.6 years; 78% women), and 429 met criteria for TRD. Thoughts of suicide and suicide attempts were more common among TRD patients (38.7%) compared with non-TRD patients (24.9%; P <0.0001), according to the current disease status questionnaire. The C-SSRS showed that lifetime suicidal behavior was significantly more common among TRD patients than non-TRD patients (13.8% vs 10.0%; P = 0.0384). Compared with non-TRD patients, TRD patients showed significantly greater adverse impacts on QoL (EQ-5D-5L), more severe depression (PHQ-9), and greater functional impairment (SDS). Conclusion: TRD patients in clinical sites from Mexico, Colombia, Brazil, and Argentina were more likely to experience suicidality and negative effects on HRQoL than non-TRD patients. Trial registration: ClinicalTrials.gov identifier: NCT03207282